Palemonídeos do Brasil (Crustacea - Decapoda - Natantia) - Corrêa, Maria Margarida Gomes (1977)
Include all species of family PALAEMONIDAE which occur in brazilian waters.This paper consists essentially of an introduction, a historical account of the family in Brazil, its systematic, conclusions, bibliography and twenty eight plates,corresponding to the species studied. The systematic section deals with descriptions, keys for classification of subfamilies, genera, subgenera and species. For each species is mentioned its characteristics, as well as, coloration, type locality, geographic distribution, size of the specimens examined and other remarks. ln the conclusions the species are divided according their habitat. Those living in freshwater are placed within the Brazilian hydrographic basins. The validity of four species is discussed, and the occorence of three species not yet recorded from Brazil is mentioned.